Papaya Root Gel for Burn Healing: Modulation of TNF-α and VEGF - Lusiana, Melissa Catherine; Vethatilova (International Journal of Science and Society, 2025)
Burn injuries are a major clinical concern due to their complex pathophysiology, prolonged recovery, and risk of complications. Conventional therapies, although widely applied, often present limitations such as delayed healing, microbial resistance, cytotoxicity, and adverse effects, thereby necessitating the search for safer and more effective alternatives. Natural products have attracted considerable attention as sources of bioactive compounds that may accelerate tissue repair while minimizing complications. Papaya (Carica papaya L.) root has been traditionally recognized for its antioxidant, antimicrobial, and anti-inflammatory activities, yet its therapeutic potential in burn wound management remains underexplored compared to other plant-derived agents. This study was designed to formulate and evaluate a topical gel containing papaya root extract as a candidate therapy for second-degree burns. The gel was prepared through ethanol extraction and standard pharmaceutical formulation, followed by in vivo evaluation in experimental models. Parameters assessed included wound contraction, epithelialization period, and expression of molecular markers relevant to inflammation and angiogenesis, particularly TNF-α and VEGF. Results demonstrated that papaya root gel enhanced wound closure, tissue regeneration, and neovascularization compared to control, suggesting its ability to modulate inflammatory pathways, reduce oxidative stress, and stimulate vascular remodeling. These findings provide evidence that papaya root extract represents a promising, accessible, and cost-effective therapeutic approach for burn wound healing, with potential advantages over conventional agents. Further studies, including clinical trials, are recommended to validate efficacy and ensure safety for human application.